Beberapa Aspek Pemikiran Syeikh Daud Bin 'Abdullah al-Fatani Dalam Perbankan Islam: Tumpuan Kepada Furu’ al-Masa’il - Borhan, Joni Tamkin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2002)
This article discusses about Syeikh Daud bin 'Abdullah al-Fatani, a great faqih and thinker of the Malay archipelago and his contribution to Islamic transactions. He wrote a number of fiqh books which cover a variety of topics on Islamic transactions. In his works, Furu' al-Masa'il, Syeikh Daud explained some aspects of the principles of Islamic banking activities such as prohibition of riba in all forms of transactions, profit and loss sharing based on mudarabah and musharakah, wadi'ah, ijarah, hiwalah, daman, bay' and bay' al-salam and wakalah.